2000
DOI: 10.1246/cl.2000.232
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-Phase Synthesis of Symmetric Ketone from Alcohol over CeO2-Fe2O3 Catalysts

Abstract: Formation of 3-pentanone via oxidative dimerization of l-propanol was investigated over CeO2-based solid solution with various metal oxides. An addition of Fe2O3 into CeO2 greatly enhanced the 3-pentanone formation, and both l-propanol conversion and 3-pentanone selectivity were maximized at Fe content of 20 mol%. It was found that the CeO2-Fe2O3 effectively works as a catalyst for the formation of symmetric ketones such as 3-pentanone, 4-heptanone, 5-nonanone, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 7 publications
0
16
0
2
Order By: Relevance
“…There is no correlation between specific surface area and conversion or selectivity. In our previous papers [33,35], we reported that CeO 2 -Fe 2 O 3 was an effective catalyst for ketone formation from 1-propanol. Here, we investigated the ketonization of propanoic acid over CeO 2 -Fe 2 O 3 ( Fig.…”
Section: Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…There is no correlation between specific surface area and conversion or selectivity. In our previous papers [33,35], we reported that CeO 2 -Fe 2 O 3 was an effective catalyst for ketone formation from 1-propanol. Here, we investigated the ketonization of propanoic acid over CeO 2 -Fe 2 O 3 ( Fig.…”
Section: Characterizationmentioning
confidence: 96%
“…Alcohols, aldehydes, and esters are also converted into ketones through dimerization in the presence of CeO 2 and ZrO 2 [5,[31][32][33][34][35][36][37]. In our previous study [35], 1-propanol, propanal and propyl propanoate were converted into 3-pentanone in the presence of CeO 2 -Fe 2 O 3 catalysts.…”
Section: Introductionmentioning
confidence: 92%
“…Depletion in fossil fuel and increased concerns on the environment stimulate replacing petroleum with renewable resources. Several researchers including us have suggested that bioethanol is a promising renewable platform chemical to yield various C3 and C4 compounds [2][3][4][5][6][7][8][9][10][11][12][13]. The present study was thus devoted to the conversion of ethanol to propene.…”
Section: Introductionmentioning
confidence: 99%
“…[96][97][98] Alcoholes lineales como el etanol, 1-propanol, 1-butanol, 1-pentanol o 1hexanol se transforman a acetona, 3-pentanona, 4-heptanona, 5-nonanona y 6undecanona respectivamente sobre catalizadores de MgO, CeO2-MgO, CeO2-Fe2O3 y óxido de Sn-Ce-Rh. [92,[99][100][101] Alcoholes ramificados como el 2-metilpropanol o alcoholes aromáticos como el 2-fenil-1-etanol también reaccionan en presencia de CeO2-Fe2O3, MgO y CeO2-MgO. [93,100] Por otro lado, se ha demostrado que alcoholes secundarios como el 2propanol o el 2-metil-2propanol no se combinan formando cetonas sobre CeO2-MgO.…”
Section: Descarboxilación Cetónica De Aldehídos Y Alcoholesunclassified
“…[92,[99][100][101] Alcoholes ramificados como el 2-metilpropanol o alcoholes aromáticos como el 2-fenil-1-etanol también reaccionan en presencia de CeO2-Fe2O3, MgO y CeO2-MgO. [93,100] Por otro lado, se ha demostrado que alcoholes secundarios como el 2propanol o el 2-metil-2propanol no se combinan formando cetonas sobre CeO2-MgO. [93] También se ha reportado la autocondensación de dioles de alcoholes primarios como el 1,6-hexanodiol a ciclopentanona sobre varios óxidos mixtos a base de CeO2.…”
Section: Descarboxilación Cetónica De Aldehídos Y Alcoholesunclassified